The Effect Of The Problem Based Learning Model Integrated With Virtual Lab On Students' Learning Outcomes In Dynamic Electricity Material - Mentari Putri Momongan; Rolles Nixon Palilingan; Jovialine Albertine Rungkat; H. Tanaumang; M. Rengkuan; Tiurlina Siregar (PT. AHLAL PUBLISHER NUSANTARA, 2026)
AbstractThe Effect of Problem Based Learning Model Integrated with Virtual Lab on Student Learning Outcomes in Dynamic Electricity Material. Thesis. Science Education Study Program, Postgraduate Program, Manado State University.This study aims to determine the effect of the Problem-based learning (PBL) model, the use of Virtual Lab, and the integration of PBL and Virtual Lab models on student learning outcomes in dynamic electricity material. The study was conducted at SMK Negeri 1 Langowan using a quantitative approach with a quasi-experimental method. The study sample consisted of four treatment groups, namely the control class, PBL class, Virtual Lab class, and PBL class integrated with Virtual Lab. Learning outcome data were obtained through multiple-choice tests that have met the validity and reliability criteria. Data analysis was carried out using descriptive statistics, normality tests, homogeneity tests, one-way ANOVA tests, and Tukey's advanced tests at a significance level of 0.05. The results of the study showed that all data were normally distributed and homogeneous. The average posttest score in the control class was 69.50, the PBL class was 80.50, the Virtual Lab class was 81.50, and the PBL integrated Virtual Lab class was 86.75. The results of the ANOVA test showed a significant difference between the treatment groups (Sig. = 0.000 < 0.05). The results of the Tukey further test showed that the PBL, Virtual Lab, and integration models provided higher learning outcomes than conventional learning. In addition, the PBL integrated Virtual Lab class obtained the highest learning outcomes and was significantly different from the PBL class and the Virtual Lab class.It was concluded that the Problem-based learning model integrated with Virtual Lab had a positive and significant effect on student learning outcomes in dynamic electricity material, so it could be used as an effective learning alternative to improve student learning outcomes.Keywords: Problem based learning, Virtual Lab, learning outcomes, dynamic electricity.